The Influence Of Perceived Value, Brand Communication, And Brand Image On Consumer Trust In The Honda Brand - Maghfiroh, Jani Putri; Hapsari, Vega; Anugraheni, Vivid; Emyrasari, Kiki; Mursid, Ali (Magister Manajemen STIE Bank BPD Jateng, 2025)
This study aims to analyze the influence of perceived value and brand communication on brand trust, with brand image serving as a mediating variable in the context of the Honda brand. Using a quantitative approach, data were collected from 200 respondents who are consumers of Honda products. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results indicate that perceived value has a positive and significant effect on brand trust, as well as a positive and significant effect on Honda’s brand image. Moreover, brand image mediates the relationship between perceived value and brand trust. In addition, brand communication is found to have a positive and significant effect on both brand image and brand trust. The study also confirms that brand image has a positive and significant effect on brand trust and plays a mediating role in the relationship between brand communication and brand trust. These findings underscore the strategic importance of building strong brand image as a bridge between value perception,communication efforts, and consumer trust in the Honda brand.